2022
DOI: 10.1136/bmjopen-2021-054169
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of healthcare providers for e-hospitals: a cross-sectional analysis in China before the COVID-19 period

Abstract: ObjectivesThe growth and development of smartphones and eHealth technologies have enabled the potential for extended care hospitals (e-hospitals) in China in order to facilitate the success of a primary healthcare centre (PHC)-based integrated delivery model. Although the adoption of e-hospitals is essential, few studies have directed their research towards understanding the perspectives of healthcare providers. This study aims to identify the current readiness of healthcare providers to adopt e-hospital techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…The "inverted triangle" of health resource allocation in China has been the usual course of medical care-seeking behavior (99)(100)(101). By comparing medical institutions at various levels in HMS, we further found that the levels of efficiency presented the same form of an "inverted pyramid."…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The "inverted triangle" of health resource allocation in China has been the usual course of medical care-seeking behavior (99)(100)(101). By comparing medical institutions at various levels in HMS, we further found that the levels of efficiency presented the same form of an "inverted pyramid."…”
Section: Discussionmentioning
confidence: 77%
“…The “inverted triangle” of health resource allocation in China has been the usual course of medical care-seeking behavior ( 99 101 ). By comparing medical institutions at various levels in HMS, we further found that the levels of efficiency presented the same form of an “inverted pyramid.” The regional differences in the allocation efficiency of public health resources ( 102 ), coupled with hierarchical heterogeneity in HMS, are of particular concern in China.…”
Section: Discussionmentioning
confidence: 99%
“…They could turn to medical platform apps to reach these goals instead of turning to social connections. Scholars have found that reputation building strongly incentivizes doctors to use medical platform apps ( 33 ). The interviewees’ responses in our study provided further support for this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation system to understand such factors may help inform clinicians of patients' access to technology, digital readiness, and specific needs. Such a tool might be used to identify barriers to care and guide management 75 . Finally, bandwidth and proper equipment must be provided to underserved communities by the government and policymakers to address the digital divide 74 …”
Section: Discussionmentioning
confidence: 99%
“…Such a tool might be used to identify barriers to care and guide management. 75 Finally, bandwidth and proper equipment must be provided to underserved communities by the government and policymakers to address the digital divide. 74…”
Section: Digital Readinessmentioning
confidence: 99%